Skill-Biased Liberalization: Germany's Transition to the Knowledge Economy. (March 2022) - Diessner, Sebastian; Durazzi, Niccolo; Hope, David
This article conceptualizes the evolution of the German political economy as the codevelopment of technological and institutional change. The notion of skill-biased liberalization is introduced to capture this process and contrasted with the two dominant theoretical frameworks employed in contemporary comparative political economy scholarship—dualization and liberalization. Integrating theories from labor economics, the article argues that the increasing centrality of high skills complementary in production to information and communications technology has weakened the traditional complementarity among specific skills, regulated industrial relations, and generous social protection in core sectors. The liberalization of industrial relations and social protection is shown in fact to be instrumental for high-end exporting firms to concentrate wages and benefits on increasingly important high-skilled workers. Strong evidence based on descriptive statistics, union and industry documents, and twenty-one elite interviews is found in support of the article's alternative perspective.